Indonesia-Malaysia Collaborative Policy to Address the Issue of Education for Indonesian Migrant Worker Family in Sabah Malaysia - Muhammad Indrawan Jatmika (Future Science, 2022)
This paper focuses on the challenges faced by Indonesian migrant workers and their families in Sabah, Malaysia, particularly with regard to education. Due lack of access to educational resources, many Indonesian children are unable to access quality education in Sabah. The paper proposes a collaborative policy between the Indonesian and Malaysian governments to address this issue in the form of providing educational facilities in the form of Indonesian Sabah schools which operate not only in the city center but in several places that were initially difficult for the children of migrant workers to reach. The proposed policy aims to improve the education outcomes of Indonesian migrant worker families in Sabah. The paper argues that a collaborative approach between the two governments is necessary to address this issue, as it requires coordinated efforts to overcome the various challenges faced by Indonesian migrant worker families. Overall, the paper highlights the importance of addressing the issue of education for Indonesian migrant worker families in Sabah and proposes a collaborative policy as a way forward. By improving the education outcomes of these families, the policy aims to promote their social and economic integration and enhance their overall well-being.